TOPICALITY OF COMMUNICATION TECHNOLOGIES AND INFORMATION (ICT) IN TEACHERS LIFELONG LEARNING AND TEACHING - Campechano Covarrubias, Juan (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This work is an advance of research in process about how is the incorporation for the use of Information Technologies and Communication (ICTs) by teachers of basic education in Jalisco State in their educational practice. The problematicalis delimited, by two factors: the level of infrastructure and equipment of schools and on the other hand, the attitudes of teachers towards ICTs.It seek investigate as the main purpose, how the teachers appropriated technologies from different programs for the use of ICTsthat has implemented by the Secretary of Public Education in their teaching. It is assumed that the reforms are not hegemonic mechanisms that permeate the educational practices but are contexts, attitudes that enable to teachers of basic education the differentiated appropriation of ICT.